Photovoltaics gaining greater visibility. - Benner, J.P (IEEE spectrum)
Photovoltaics technology is well established as a reliable and economical source of electricity in small, scattered applications, far from urban centers. Now it is looming larger in size and public awareness. The author discusses the role of photovoltaic systems in the USA, their operating principles and developments for the future